Suspicion as Symbol: Hermeneutic-Semiotic Construction of Fraud as Forensic Doctrine in the Indonesia Stock Exchange (2004–2024) - Apollo; Caturida Meiwanto Doktoralina (Green Publisher, 2025)
This article proposes the Symbolic Suspicion Theory (SST) to reconceptualize forensic audit discourse in the Indonesia Stock Exchange (IDX) from 2004 to 2024. Drawing on semiotics, hermeneutics of suspicion, and critical discourse theory, the research analyzes 20 years of public audit reports, IPO fraud cases, regulatory documents, and news archives. Rather than treating fraud as a purely factual deviation, SST interprets suspicion as a symbolic form that operates across myth, ethics, and institutional legitimacy. Using the lenses of Cassirer’s mythic logic, Ricoeur’s metaphorical discourse, and Derrida’s différance, the study identifies four temporal layers: (1) 2004–2008’s proto-suspicion amidst liberalization; (2) 2009–2014’s institutionalization of suspicion via corporate governance; (3) 2015–2020’s affective turn during the tech unicorn era; and (4) 2021–2024’s ESG-driven symbolic inflation of audit ethics. Findings demonstrate that suspicion functions analogously to religious heresy in pre-modern law: necessary to demarcate truth, not merely expose deception. SST challenges positivist audit paradigms by framing fraud not only as a forensic target, but as a hermeneutic object embedded in cultural narratives, regulatory myths, and affective language. The audit report, thus, must be read as a symbolic text layered with moral, political, and epistemic tensions. The study concludes that forensic accounting education must integrate symbolic-literary and interpretive competencies to critically engage the evolving semiotics of suspicion.